PREVALENCE OF MENSTRUAL MIGRAINE AND THE EFFICACY OF SUMATRIPTAN ADMINISTRATION: Prevalensi Migrain Menstrual dan Efikasi dari Pemberian Sumatriptan - Maridsky, Aldilla Afifie Putri; Sudibyo, Devi Ariani; Qurnianingsih, Ema; Dyah Kencono Wungu, Citrawati (Jurnal Berkala Epidemiologi, 2024)
Background: Menstrual migraine is a primary headache that often attacks women of reproductive age. This type of migraine has high severity and is resistant to treatment. Therefore, an effective treatment is needed to treat this menstrual migraine. Sumatriptan has been shown to have a better effect as an acute treatment for menstrual migraine patients. Purpose: This study aims to determine the prevalence and effectiveness of sumatriptan as a therapy for menstrual migraine. Methods: This research is based on a literature review following predetermined inclusion criteria. First, a literature search was carried out adhering to the PRISMA flow in 4 databases: Pubmed, Science Direct, ProQuest, and ClinicalTrial.co. Results: Based on keywords, 267 studies were found in the literature search. However, only three studies covering 845 participants met the predetermined inclusion criteria. The average age of menstrual migraine patients in the three studies was 37 years. These three studies of sumatriptan revealed a significant effect in providing a pain-free response in menstrual migraine patients. These three studies also showed that sumatriptan 100 mg has a higher level of effectiveness in providing a pain-free response in menstrual migraine sufferers and was preferably given during mild attacks. Conclusion: These three studies indicate that typically, women who suffer from menstrual migraines are of reproductive age. Additionally, this study shows that using sumatriptan as an acute therapy significantly helps provide a pain-free response in menstrual migraine patients.